Impact of Obesity and Underweight on Surgical Outcome of Lumbar Disc Herniation. (12th January 2014) - Omidi-Kashani, Farzad; Ghayem Hasankhani, Ebrahim; Rafeemanesh, Ehsan; Seyf, Parham; Attarchi, Hassan; Rahimi, Mohammad Dawood; Khanzadeh, Reza
Abstract : Background. The relationship between underweight and lumbar spine surgery is still unknown. Aim. To evaluate the effect of underweight versus obesity based on surgical outcome of lumbar disc herniation. Material and Method. In this retrospective study, we evaluated 206 patients (112 male and 94 female) with a mean age of37.5 ± 3.1 years old (ranged 20–72) who have been surgically treated due to the refractory simple primary L4-L5 disc herniation. We followed them up for a mean period of42.4 ± 7.2 months (ranged 24–57). We used Body Mass Index (BMI), Oswestry Disability Index (ODI), and Visual Analogue Scale (VAS) for categorization, disability, and pain assessment, respectively. We used Wilcoxon and Mann-WhitneyU tests for statistics. Results. Surgical discectomy in all weight groups was associated with significant improvement in pain and disability, but intergroup comparison showed these improvements in both underweight and obese groups and they were significantly lower than in normal weight group. Excellent and good satisfaction rate was also somewhat lower in both these ends of weight spectrum, but statistically insignificant. Conclusion. Both obesity and underweight may have adverse prognostic influences on the surgical outcome of lumbar disc herniation, although their impact on subjective satisfaction rate seems to be insignificant.